(untitled) (Modern Problems of Metallurgy, 2022)
The oxygen-converter process is accompanied by the release of a significant amount of off-gases, that under the conditions of postcombustion form a torch over the neck of the converter. It is an additional source of heat in the converter. Change the torch nature corresponds the peculiarities of the heat blowing. However, it is difficult to register and analyze the torch due to the significant temperature above the neck of the unit and the large amount of dust released during the blowing. And, if small particles of dust can considerably heat up in real conditions of the converter and strengthen indicators of a torch, much bigger particles can interfere with it. It was conducted a physical modeling on a single gas torch of 250-300 mm particles of different chemical composition (corresponding to the oxygen-converter process) influence on the possibility to register the physical characteristics of the postcombustion torch: heat transfer, luminosity (brightness) and electrical characteristics. Visually, it was established that the direct supply of non-oxidizing solid particles to the burning torch turns the burning flame in yellow or yellow-orange color and the flame increases in size due to incomplete combustion of the fuel mixture compared to pure combustion (without dust). This manifestation is characteristic of particles of oxides of silicon, calcium and magnesium and iron (III) oxide. Particles that can be oxidized by contact with a burning torch, in addition to increasing the visible part, cause a significant increase in the visual brightness of the flame.